The Threonine Requirements and its Effects on Growth Performance and Gut Morphology of Broiler Chicken Fed Different Levels of Protein - Zaefarian, F.; Zaghari, M.; Shivazad, M. (International Journal of Poultry Science, 2008)
An experiment was conducted to determine the effects of dietary threonine (Thr) and crude protein (CP) on growth performance, gut measurements and morphology and to estimate Standardized Ileal Digestible (SID) Thr requirements of Ross 308 males at 0-21 days of age. The SID Thr levels were 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 and 1.1% with two levels of protein 16 and 19%. Chicks were randomized into 64 battery pens (5 chicks per replicate). FI was lower for broiler given the high CP diets compare to those fed on the low CP diets. BWG and FCR improved up to 0.7% Thr in both CP levels. Weight gain improved non-linearly suggesting optimum dietary SID Thr levels between 0.89 and 0.84% (quadratic) at 16 and 19% ideal protein, respectively. Significant interaction was found between CP and Thr on relative weight and length of duodenum and jejunum (p